Intestinal and Extraintestinal Manifestations of Inflammatory Bowel Disease - L. S. Mkrtchyan; V. A. Kosenko; K. E. Nikitina (Медицинский вестник Юга России, 2012)
The problem of inflammatory bowel disease draws constant attention not only of gastroenterologists but also surgeons - coloproctologists and other doctors. These related to the growing incidence of this pathology in the world, as well as the diversity of clinical manifestations, including severe extraintestinal manifestations and complications, which in clinical practice, faced not only gastroenterologists. In most cases, inflammatory bowel disease leads to permanent disability cases, which makes this problem not only medical but also socially relevant.